Nurse‐led primary health care for homeless men: a multimethods descriptive study. (21st December 2017) - Roche, M.A.; Duffield, C.; Smith, J.; Kelly, D.; Cook, R.; Bichel‐Findlay, J.; Saunders, C.; Carter, D.J.
Abstract : Aim: To explore the primary healthcare needs and health service use of homeless men in inner Sydney. Background: People experiencing homelessness have greater health needs than the general population and place high demands on tertiary care, which is expensive and may not be the optimum service for their needs. Accessible, approachable and affordable primary healthcare services could improve the health of homeless persons and potentially decrease costs to the healthcare system. Methods: A multimethod design using a cross‐sectional survey (n = 40) and administrative data (n = 2 707 daily summaries) collected from a nurse‐led primary healthcare clinic for homeless men in Sydney. Findings: Survey respondents were aged 27‐76 years. Health problems reflected multimorbidity, with mental health issues present in almost all respondents. The majority had attended the clinic more than 20 times in the past year and said the services, treatments and referrals helped them avoid the emergency department. Administrative data indicated that medication administration was the most frequent service provided. Referrals to other health services doubled over the 7‐year period. Discussion: Multiple morbidities, particularly mental health issues, are associated with homelessness. A proactive approach by nurses including preventative services appeared to overcome barriers to health service use. Conclusion: This nurse‐led primary healthcare clinic highlights the importance of providing services to homeless men with multiple comorbidities. Respect and trust in addition to easy access to health services appear to be important facilitators of health service use. Implications for Nursing, and Implications for Health Policy: A greater number of primary health services that collaborate with specialist services, including nurse‐led clinics, may facilitate health care for persons who are homeless, reducing the burden on acute services.